1998
DOI: 10.1271/bbb.62.148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a cDNA Encoding Asparagine Synthetase from Soybean (Glycine maxL.) Cell Cultures

Abstract: A cDNA enceding gl-tamine-dependent asparagine synthetase was isolated from dark-adapted Glycine max cell culture. The deduced amino acid seq"ence showed 76-89% fidentity with other plant sequences. The gene for asparagine synthetase is expressed predominantly in shoets as compared to roots of etiolated plants and the leyel of expression decreases following light treatment, suggesting that the gelle expression is dewn-regulated by light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…, 1996), soybean ( Glycine max , accession no. , Yamagata et al. , 1998), Arabidopsis ASN 1 ( A. thaliana , accession no. )…”
Section: Resultsmentioning
confidence: 99%
“…, 1996), soybean ( Glycine max , accession no. , Yamagata et al. , 1998), Arabidopsis ASN 1 ( A. thaliana , accession no. )…”
Section: Resultsmentioning
confidence: 99%
“…The expression of plant AS genes is usually limited to particular organs and is negatively regulated by light (Tsai and Coruzzi 1991, Yamagata et al 1998). In contrast, ShAS does not follow this typical pattern since its expression is widespread (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These cDNAs probably all encode glutamine‐dependent AS enzymes, not NH 4 + ‐dependent AS enzymes, since the purF ‐type amidotransferase domain was identified in their deduced amino acid sequences. In some species, the expression of AS genes has been found to be negatively regulated by light (Tsai and Coruzzi 1990, Lam et al. 1998, Yamagata et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that glutamine or glutamine-derived metabolites regulate AS expression in rice roots. (Küster et al 1997), soybean (Hughes et al 1997, Yamagata et al 1998, common bean (Osuna et al 1999) and rice (Watanabe et al 1996). These cDNAs probably all encode glutamine-dependent AS enzymes, not NH 4 πdependent AS enzymes, since the purF-type amidotransferase domain was identified in their deduced amino acid sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation